Implementation of The Values of Entrepreneurship in Students of SMA Negeri in DKI Jakarta - Sugiono, Sugiono; Martono, Trisno; Wardani, Dewi Kusuma (International Journal of Active Learning, 2018)
Issues relating to the role of entrepreneurship education are: 1) the increasing number of unemployed that there needs to be addressed with the improvements in education entrepreneurship; 2) education entrepreneurship serve as solutions in lowering the unemployment rate at the HIGH SCHOOL level; 3) entrepreneurship education as a means to provide learners to continue on to further education level, as well as self-employment. The purpose of this study is meant to analyze and describe about the implementation of the values of entrepreneurship in high school with a review of the three extra curricular activities IE activities, cultural and learning activities of the school. This study uses qualitative methods, data collection using a semi structured interview and observation. A summary of this research is the third such activities provide positive impact to the creation of the character of learners.